Light trapping for flexible organic photovoltaics - Park, Yoonseok; Berger, Jana; Will, Paul-Anton; Soldera, Marcos; Glatz, Bernhard; Mueller-Meskamp, Lars; Taretto, Kurt; Fery, Andreas; Lasagni, Andres Fabian; Vandewal, Koen; Leo, Karl (Proceedings of SPIE - The International Society for Optical Engineering, 2016)
Here we investigate light trapping substrates and electrodes for enhancing the performance of organic photovoltaics (OPVs). Their power conversion efficiency (PCE) can be improved by a factor of 1.16 using laser patterned PET substrates and by a factor of 1.13 using commercial, structured display films. Furthermore, we prepare light trapping electrodes using as flexible conductive polymer with embedded TiO2 nanoparticles, improving the PCE by a factor of 1.08 as compared to a neat polymer electrode. However, nano-imprinted conductive polymer electrodes does not provide light trapping effect due to the small size (50 nm) of the structures. Moreover flexible OPV devices, integrating the above light trapping elements, show non-degraded performance after bending tests.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Conductive polymer; Flexible; Light trapping; Organic solar cells; Textured substrate